Empowering Elementary Students with Community-Based Engineering: A Teacher's Experience in a Rural School District - Tugba Boz; Rebekah Hammack; Nicholas Lux; Paul Gannon (MDPI AG, 2023)
This paper presents a case study of an elementary teacher, Holly, who participated in a federally funded summer professional development (PD) program aimed at integrating community-based engineering into elementary education. The study examines how Holly's teaching practices and beliefs about teaching engineering contributed to the significant improvements in her students' attitudes toward engineering and their perceptions of engineering as a potential career. Data were collected over three years through multiple methods, including post-PD interviews, lesson recordings, and a post-teaching interview. We analyzed classroom videos using a video analysis protocol. We used open coding to analyze the interviews. Once the analysis of the interviews and videos was completed, we engaged in a sense-making process to identify connections across data points (videos and interviews). Our findings showed that Holly extensively incorporated scientific inquiry into her lessons. This approach enabled students to develop their inquiry skills and facilitated a smooth transition to engineering design activities. By connecting class activities to the local context, students were able to see the relevance of engineering to their everyday lives and take ownership of their learning. This study emphasizes the potential of community-focused engineering to foster meaningful science and engineering practices in elementary education.